Micro spray and end caps performance operating with water containing different concentrations of organic matter - da CUNHA, Fernando França; da SILVA, Thiago Ramos; Magalhães, Fernando Fagner; Ferreira, Daniel de Andréa; Silva, Simone Quintão [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2018)
Recently a micro spray and an end cap with drain valve device were launched on the market. Their main advantage is the low cost. The micro spray provides a higher percentage of irrigated area relative to the drippers and an end cap with drain valve removes all air from the pipes and minimizes obstructions of the emitters. However, these components need to be tested operating with different water quantities and qualities. Therefore, this study aimed to evaluate the performance of this micro spray and end cap with drain valve operating with water containing different concentrations of total solids. The experiment was conducted in a split plot scheme, with two end caps in the plots (conventional and with drain valve) and five total solid concentrations in the subplots (7 mg L-1, 407 mg L-1, 1007 mg L-1, 2007 mg L-1 and 4007 mg L-1) in a completely randomized design, with three replications. Sixty evaluations of the irrigation system were performed and the emitters were evaluated every application of 60 L up to a volume of 3.6 m3. The water flow rate and application uniformity were evaluated through distribution uniformity (DU) and statistical uniformity (US) coefficients. The micro spray performance was not affected by water application containing total solid concentrations below 270 and 500 mg L-1 in irrigation systems equipped with conventional end caps or with drain valves, respectively. Irrigation systems equipped with end caps with drain valve provided a better performance of micro sprays when operating with water containing total solid concentrations greater than 407 mg L-1. These end caps did not provided difference in micro spray performance when operating with public water.
Desempenho de micro spray e válvula fim de linha operando com águas contendo diferentes concentrações de material orgânico
Keywords: Application uniformity; Drip irrigation; Total solids